TINJAUAN STANDARISASI LABORATORIUM IPA BIOLOGI DI SMA NEGERI SE-KABUPATEN SOLOK SELATAN TAHUN PELAJARAN 2013/2014 - Septinurmita, Rahayu; Nursyahra, Nursyahra; Yulia Sari, Liza (Pendidikan Biologi, 2014)
Â ABSTRACTLearning biology is asset of knowledge known as the result of research and expert thought and basic skills as well that reflect to the process to accomplish its result. In this case, a medium is needed to expand the basis skills that reflects the process of scientific activity, for instance the availability of laboratory. While doing the scientific activity, a medium used should be standardized in order to accomplish the goal. The government has create the rules of using the medium and infrastructure in education that is stated in Educational Prime Minister Rule No. 24, june 28, 2007 that was started from the wide of the minimum area, the buildings, and the completeness of the medium and infrastructure of the school, the laboratory included. The good laboratory should provide various facilities and also skillful technician is really needed, in order to make the lab work easier. This research is kind of descriptive research. It is carried out in all of biology laboratory in Senior High School at South Solok in West Sumatra in the even semester on 2013/2014. The population of the research is all of Senior High School at South Solok, that is 8 schools on 2013/2014. The sample is 6 schools, they are taken by using Purposive Sampling technique. The technique of data analysis used in this research is descriptive analysis. Based on the descriptive data analysis, the questionnaire result show that the standardization of biology laboratory in there schools is about 79,9 % and based on the observation result gained is 70,7 % with a range of both result are good criterion. This result is obtained from the precentage average of questionnaire filling and observation sheet that is distributed to 6 respondents in 6 schools in South Solok on academic year 2013/2014.